Top Incomes and the Measurement of Inequality in Egypt - Hlasny, Vladimir; Verme, Paolo (World Bank, Washington, D.C., 2013)
By all accounts, income inequality in Egypt is low and had been declining during the decade that preceded the 2011 revolution. As the Egyptian revolution was partly motivated by claims of social injustice and inequalities, this seems at odds with a low level of income inequality. Moreover, while income inequality shows a decline between 2000 and 2009, the World Values Surveys indicate that the aversion to inequality has significantly increased during the same period and for all social groups. This paper utilizes a range of recently developed statistical techniques to assess the true value of income inequality in the presence of a range of possible measurement issues related to top incomes, including item and unit non-response, outliers and extreme observations, and atypical top income distributions. The analysis finds that correcting for unit non-response significantly increases the estimate of inequality by just over 1 percentage point, that the Egyptian distribution of top incomes follows rather closely the Pareto distribution, and that the inverted Pareto coefficient is located around median values when compared with 418 household surveys worldwide. Hence, income inequality in Egypt is confirmed to be low while the distribution of top incomes is not atypical compared with what Pareto had predicted and compared with other countries in the world. This would suggest that the increased frustration with income inequality voiced by Egyptians and measured by the World Values Surveys is driven by factors other than income inequality.